The overlap rate influences the microstructure and properties of laser-cladded Fe-Ni-Ti composite coatings - Wang, Zhen; Qi, Changbao; Zhang, Fengqin (Frontiers in Materials, 2024)
Single and multi-pass Fe-Ni-Ti composite coatings were prepared on the surface of 45 steel using a semiconductor laser. The microstructure and phase composition of the fusion layers were analyzed using metallographic microscopy, XRD diffraction, scanning electron microscopy, and energy dispersive spectrometry. Friction coefficients and microhardness of fusion layers with different overlap ratios were tested using a multifunctional surface performance tester and a microhardness tester. The wear performance of coatings with different overlap ratios was tested using a wear testing machine. The results indicate that when 6% Ti was simultaneously added to the Invar alloy matrix during the laser fusion of Fe-Ni-Ti alloy coatings, the phase composition of the fusion layer mainly consists of γ-[Fe, Ni] austenite, Fe3Ni2, α-Fe, and other metallic compounds.Simultaneously, in-situ formation of TiC reinforcement is dispersed in the matrix of γ-[Fe, Ni] solid solution. When the overlap ratio is 46%, the fusion layer exhibits a uniform, dense structure with fewer defects and higher coating hardness, resulting in improved wear resistance. At this point, the microhardness of the fusion layer is 450 HV, 1.5 times that of the substrate material and 2.2 times that of the base material. The friction coefficient on the coating surface is 0.412, with a percentage weight loss of 0.17%. The wear theory of the cladding layer is mainly adhesive wear, which also includes abrasive wear.